Association of dietary niacin intake with osteoporosis in the postmenopausal women in the US: NHANES 2007–2018 - Li, Li; Liang, Wankun; Deng, Bing; Jiang, Yue; Huang, Xiaomin; Zhang, Yanlin; Lu, Tianrui; Wang, Lu; Xu, Yunxiang; Chen, Guizhen (Frontiers in Medicine, 2025)
BackgroundElderly individuals with inadequate vitamin B level are at increased risk of degenerative conditions, notably cardiovascular disorders, cognitive impairments, and osteoporosis. The relationship between niacin (vitamin B3) consumption and osteoporosis risk remains a subject of debate. This study aimed to clarify the relationship between dietary niacin intake and the incidence of osteoporosis in postmenopausal women aged ≥50 years.MethodsIn this study, we gathered details on participants’ bone mineral density, osteoporosis status, dietary niacin intake, and several other critical variables. Multivariate logistic regression models were constructed to determine the association between dietary niacin intake and the incidence of osteoporosis. Restricted cubic splines were employed to further assess the linearity and explore the shape of the dose-response associations. Additionally, we performed stratified and interaction analyses to illustrate the stability of the observed relationships across different subgroups.ResultsAfter adjusting for all covariates, there was a significant inverse association with osteoporosis (OR = 0.87; 95% CI: 0.77–0.97; p = 0.016). A negative relationship was observed between dietary niacin intake and the risk of osteoporosis (nonlinear: p = 0.672). While stratified analyses revealed some differences in the association between dietary niacin intake and osteoporosis risk, these differences were not statistically significant.ConclusionDietary niacin intake exhibited an inverse correlation with the incidence of osteoporosis. The risk of osteoporosis was significantly reduced by 13% with every 10 mg/day increase in daily dietary niacin consumption among postmenopausal women.